EDUCATION AS THE PRACTICE OF FREEDOM AND THE PROSPECT OF INTEGRAL EDUCATION IN HIGHER EDUCATION - João Ricardo Silva; Tânia Suely Azebedo Brasileiro (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
In this article we discuss the idea of Education as a Freedom Practice, taking into account an emancipatory perspective of Integral Education for Higher Education. Thus, we reflect on an integral education in opposition to the hegemonic and simplistic version of an education for the market and even in opposition to that which means absorption of superior objective knowledge. The methodology used was the bibliographical research, where we sought a dynamic synthesis between Marxist authors and the colonial / postcolonial discussion. The theoretical horizon was a dialectical historical materialism, but without neglecting that knowledge is beyond the Western gaze and that science is not the only logic of valid knowledge. Given that knowledge is not only a reflection of reality, but the interpretation of this, the search for an integral education is also the search for inter-knowledge. This leads us to deacralize the university and to transform it into a place of building democratic relations. Keywords: Integral Education. Practices of freedom. Higher Education.